Grain‐Slip Derived Network Topology to Remarkable Strength–Toughness Combination of Perovskite Film for Flexible Solar Cells. Issue 39 (25th August 2022) - Lu, Zheng; Lou, Yanhui; Xiao, Lingbo; Xu, Xiaoli; Wang, Chen; Li, Lutao; Su, Xiaodong; Zou, Guifu
Abstract: The toughness and strength are generally mutually exclusive for most materials. Although the biological materials in nature such as wood, bone, and nacre exhibit outstanding toughness by forming hierarchical multiscale (nano to macro) structures, it is a huge challenge to simultaneously obtain excellent strength and toughness from material synthesis. Here, one kind of network topology is observed by introducing sodium hyaluronate into organometallic halide perovskite film to greatly improve its strength and toughness. The grain slip and grain subdivision under tensile stress are schemed to dissipate the system energy and endow the perovskite film with remarkable toughness. Meanwhile, the subdivided grains linked by sodium hyaluronate through strong interaction result in high strength of perovskite film. As a result, the perovskite films exhibit robust enhancements with the elongation at break from 1.58% to 5.02% and the fracture strength from 23.13 to 55.25 MPa. It is worth noting that the efficiency of inverted flexible perovskite solar cells reaches 20.01% as well as maintains 90% of the initial efficiency after 6000 cycles of bending at a 2 mm curvature radius. This work devises a topology structure to overcome the conflict between toughness and strength of perovskite films for wearable electronics. Abstract : Network topology derived from grain subdivision and grain slip enables simultaneous robust toughness and strength of perovskite films with the elongation at break of 5.02% and the fracture strength of 55.25 MPa, respectively. The flexible solar cells achieve a champion power conversion efficiency of 20.01% and remaining 90% of the initial efficiency after bending 6000 cycles at the 2 mm curvature radius.